Aspects of Juvenile and Adolescent Environment Predict Aggression and Fear in 12-Month-Old Guide Dogs - Serpell, James A.; Duffy, Deborah L. (Frontiers in Veterinary Science, 2016)
Maturational changes in behavior, and the possible influence of the puppy-raising environment on behavioral development, were investigated in a total sample of 978 prospective guide dogs belonging to 4 different breeds/crosses. All dogs belonged to the same guide dog organization, and had been exposed to similar early environmental influences prior to being assigned to puppy-raising households at 7-8 weeks of age. Behavioral data were collected from puppy-raisers when the dogs were 6 and 12 months old using the C-BARQ©, a standardized, validated, and widely used survey instrument that measures the frequency and/or severity of most common behavior problems in dogs. Information about the puppy-raising environment was obtained from puppy-raisers using a standardized questionnaire shortly before the dogs were returned to the guide dog organization for training. Data were analyzed using both univariate and multivariate statistics (binary logistic Generalized Estimating Equations modeling and Generalized Linear Modeling). The findings demonstrated specific maturational changes in behavior between 6 and 12 months of age. In particular, German Shepherd Dogs (GSDs) displayed an increase in stranger-directed aggression compared with the other breeds/crosses between 6 and 12 months of age. Several aspects of the puppy raising environment were associated with puppies’ C-BARQ scores at 12 months of age. Being reared by more experienced puppy-raisers, and living in households with at least one other dog, were associated with positive effects on a number of puppy behaviors. In contrast, puppies that had been frightened by a person or threatened by another unfamiliar dog, showed significantly worse scores for fear of strangers and dogs, respectively. Being frightened by a person, being reared by less experienced puppy-raisers, and/or in households without other pets was associated with less successful training outcomes. The relevance of these findings to current guide dog breeding and husbandry practices is discussed.